SISTEM PENANGANAN PERILAKU INDISIPLINER SANTRI DALAM TINJAUAN ILMU BIMBINGAN DAN KONSELING (Studi Kasus di TMI Putra PP. Al-Amien Prenduan Sumenep) - Yanto Yanto (Fakultas Agama Islam Universitas Islam Madura, 2021)
Disciplinary behavior is often found in the world of education, including Islamic boarding schools. The occurrence of disciplinary behavior in Islamic boarding schools is caused by many factors, such as students' family background factors, motivational factors, and the influence of friends. This paper aims to explain the implementation of handling student disciplinary behavior, especially its relevance in the perspective of the guidance and counseling system. The type of research used is qualitative using a case study approach, the informants in this study were selected using the snowball sampling technique. The results showed that the implementation of handling students' disciplinary behavior was carried out by forming a Santri Organization (Organtri) which in this case was carried out by the Organtri Consideration Council (MPO) section by implementing a gradual punishment system. In general, the handling of disciplinary behavior among TMI Putra PP students. Al-Amien is relevant to the guidance and counseling system, where in the implementation of the gradual punishment system there are pre-guidance activities and guidance activities.